The importance of adopting Public-Private Partnerships as a new managerial practice to enhance the Public Health Institution’s efficiency: Obstetric service in Algeria as a model - Zouleikha Rahmani,; Ouafa Rais, (Journal of North African Economies, 2025)
This study aims to highlight the importance of adopting Public-Private Partnership (PPP) as a mechanism from New Public Management (NPM) paradigm based on Total Quality Management (TQM) approach, to enhance the efficiency of Public Health Institution and as a collaborative method where both of stakeholders work together to enhance healthcare service’s quality. it focuses on obstetric services provided to persons socially insured or their spouses in the state of Batna, within the framework of PPP that has been adopted by Algeria following Executive Decree No 20/60. To meet the study's objectives, the researchers relied on the analytical descriptive method, using interviews and documentary analysis as tools to analyze the legal reference and health indicators in study area for the period (2019-2023). The study pointed out that PPPs play a crucial role in improving the efficiency of public health institutions. However, it is necessary to create adequate conditions for a healthy partnership.